Developing Students' Dialectical Thinking Through Establishing Cause-And Effect Relationships In The Chemistry Educational Process - Azamovna, Kadyrova Musharrafkhan (Researchparks Publishing, 2025)
This article presents an in-depth analysis of how the development of students’ dialectical thinking can be enhanced through the identification and application of cause-and-effect relationships within the chemistry curriculum. It highlights the importance of analytical strategies based on causal reasoning to foster students’ cognitive competence, critical and creative thinking, and ability to draw scientific inferences. The paper explores theoretical and methodological foundations, practical implementation tools such as algorithmic learning cards, and modeling techniques used to develop these competencies. The study concludes that integrating such strategies into the chemistry education process significantly strengthens learners’ ability to engage in knowledge synthesis, prediction, and scientific problem-solving.